Holding the Hunger Games Hostage at the Gym: An Evaluation of Temptation Bundling - Milkman, Katherine L.; Minson, Julia A.; Volpp, Kevin G. M. (Management Science, 2014)
We introduce and evaluate the effectiveness of temptation bundling—a method for simultaneously tackling two types of self-control problems by harnessing consumption complementarities. We describe a field experiment measuring the impact of bundling instantly gratifying but guilt-inducing “want” experiences (enjoying page-turner audiobooks) with valuable “should” behaviors providing delayed rewards (exercising). We explore whether such bundles increase should behaviors and whether people would pay to create these restrictive bundles. Participants were randomly assigned to a full treatment condition with gym-only access to tempting audio novels, an intermediate treatment involving encouragement to restrict audiobook enjoyment to the gym, or a control condition. Initially, full and intermediate treatment participants visited the gym 51% and 29% more frequently, respectively, than control participants, but treatment effects declined over time (particularly following Thanksgiving). After the study, 61% of participants opted to pay to have gym-only access to iPods containing tempting audiobooks, suggesting demand for this commitment device. This paper was accepted by Uri Gneezy, behavioral economics.